A Semiotic Study of Faruq's Poem “Haninun” Juwaidah from Michael Riffaterre's Perspective - Mhd Muzakki; Arif Mustofa (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This qualitative study aims to reveal and explain the unity of meaning contained in Haninun's (حنين) poetry through Michael Riffaterre's semiotic approach, specifically by utilizing heuristic reading, hermeneutic reading, and tracing matrix structures, models, and variants. The data analysis technique used is Miles and Huberman's analysis technique. The results of the semiotic analysis of Faruq Juwaidah's poem Haninun using Michael Riffaterre's perspective show that the poetic meaning in the text is constructed through the process of heuristic reading, hermeneutic reading, and mapping the relationship between matrix, model, and variant. The results of heuristic reading show that the lexical structure of the poem is dominated by the forms ism, harf, and a number of verbs in fi‘il madhi and fi‘il mudhari, which linguistically indicate the poet's tendency to use diction with emotional, relational, and existential nuances.